2000
DOI: 10.1080/026990500413731
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcome for African Americans and Hispanics treated at a traumatic brain injury model systems centre

Abstract: Unmarried African American males, with an average age of 35 years, predominated at this institution. The primary mechanism of injury was motor vehicle accidents. The majority of patients had, at least, a high school education or passed an equivalency exam, were employed at the time of their injury and were discharged to their prior private residence. While half of the patients met criteria for moderate-to-heavy alcohol consumption, only one-third of the patients reported a history of pre-morbid illicit drug us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…Burnett et al (2000) articulate that African Americans with TBI were high school educated, expelled, dropped out before graduation, labeled as special needs, and failed a grade at some point during their school education. Additionally, Burnett et al (2000) provide more details about Black people in the study regarding substance abuse, previous encounters with the police, and resulting arrests. However, Burnett et al (2000) did not justify the reasoning behind providing those details about Black people.…”
Section: Resultsmentioning
confidence: 99%
“…Burnett et al (2000) articulate that African Americans with TBI were high school educated, expelled, dropped out before graduation, labeled as special needs, and failed a grade at some point during their school education. Additionally, Burnett et al (2000) provide more details about Black people in the study regarding substance abuse, previous encounters with the police, and resulting arrests. However, Burnett et al (2000) did not justify the reasoning behind providing those details about Black people.…”
Section: Resultsmentioning
confidence: 99%
“…23 Studies have found that minorities affected with TBI have different demographic and injury characteristics and poorer functional outcomes than injured non-minorities. 2428 The discrepancy in functional outcomes has been related to less medical care provided to minorities 26, 28, 29 and to socio-demographic and injury factors. 24, 25, 30 Because minorities and non-minorities afflicted with TBI differ in many aspects, it is necessary that TBI research studies consider an adequate representation of both groups in order to improve the outcomes of the whole population.…”
Section: Discussionmentioning
confidence: 99%
“…In the civilian population, risk will vary with age, gender and racial group. A higher proportion of African Americans, for example, experience brain injuries from assaults (Arango-Lasprilla et al, 2007;Burnett Silver, Kolakowsky-Hayner, & Cifu, 2000;Hart, Whyte, Polansky, Kersey-Matusiak, & Fidler-Sheppard, 2005;, while individuals above the age of 65 or below the age of 4 experience a disproportionate number of TBIs caused by falls (Sosin, Sniezek, & Thurman, 1996).…”
Section: Definition Of Tbimentioning
confidence: 99%
“…Demographically, African Americans and Hispanics who experience a TBI are more likely to be younger, male, unemployed pre-injury, have lower levels of education, unmarried, have lower incomes pre-injury and less likely to have health insurance as compared to Whites (ArangoLasprilla et al, 2007;Burnett et al, 2000;Hart et al, 2005;Johnstone et al, 2003;Shafi et al, 2007a;. Acts of violence are also more prominent cause of injury, with African Americans and Hispanics being 3 -4 times more likely sustain a TBI through acts of violence relative to Whites (Arango-Lasprilla et al, 2007;Burnett et al, 2000;Hart et al, 2005;.…”
Section: Ethnic and Racial Disparities In Outcomes Following Tbimentioning
confidence: 99%
See 1 more Smart Citation